HUBUNGAN PERCAYA DIRI DENGAN KEMAMPUAN KOMUNIKASI ANAK TUNARUNGU KELAS V DI SLB - ARDIYANTI WAHYU LESTARI, NURINA (Jurnal Pendidikan Khusus, 2016)
ABSTRACT  The confident of hearing impairment children was to be able to do something suitable with their own ability, able to always be optimist by thinking positively and solve every problem without hesitant toward themselves. Communication ability was the children’s ability in interacting with the teacher and discussed with their peers. Based on the result of observation and interview with the teacher of class V in SDLB-B Karya Mulia II about self-confident, there was indication that hearing impairment children was less active in communicating so that they tended to give in more to their active friends during the learning process was running. It described that the children’s communication ability was not maximum yet. Hearing impairment children were those who had damage in hearing sense so it caused lack of lost of hearing either a part or whole.  This research had purpose to observe whether there was relationship of self confident with communication ability of hearing impairment children of class V in SDLB-B Karya Mulia II Surabaya or not. This research used quantitative approach with non-experiment kind using correlation arrangement with 10 students. The data analysis in this research was statistic non parametric using correlation formula of Spearman Rank.  The results of data analysis indicated rho counted = 0,71 > rho table = 0,648 to significant level 5%. It proved that Ho was refused and Ha was accepted. Based on the explanation above it could concluded that there was significant relationship self confident with communication ability of hearing impairment children of class V in SDLB-B Karya Mulia II Surabaya.   Keywords: Self confident, communication ability.